Socio-psychological mechanisms of the modern family image - Mirzayeva Sayyora Rustamovna (Psychohealth: Scientific Journal of Psychology and Mental Health, 2025)
Purpose: This study aims to examine the socio-psychological mechanisms that shape the modern family image, emphasizing how emotional, communicative, and cognitive processes interact within contemporary social dynamics. The research seeks to identify the psychological and sociocultural determinants such as empathy, value internalization, and media influence that define the perception, identity, and stability of the modern family. Methodology: The study uses mixed qualitative–descriptive and quantitative methods grounded in socio-psychological and cultural theories. Data from 150 participants aged 20–50 were gathered through analysis, surveys, interviews, and observation. Descriptive statistics, correlation tests, and thematic analysis were applied to assess emotional intelligence, communication, and family perception. Results: Findings reveal that the modern family image is formed through the interaction between social structures and psychological mechanisms such as empathy, emotional regulation, and communicative competence. Families with higher emotional awareness and adaptive communication display stronger resilience and harmony amid societal transformation and digital influence. Media exposure plays a dual role, both shaping and distorting the family’s self-presentation. Conclusion: The study concludes that the modern family functions as a dynamic psychological system, balancing internal emotional cohesion with external social expectations. Its image reflects both authenticity and adaptation to modernization, emphasizing the need for emotional literacy and social responsibility. Limitations: The study’s scope is limited to specific demographic groups and self-reported data, which may not capture broader cross-cultural variations. Contribution: This research contributes to family psychology by integrating emotional, cultural, and communicative dimensions, offering practical insights for policymakers, educators, and counselors to strengthen family identity and resilience in the digital age.